Diabetes mellitus and pregnancy: diagnosis and treatment - Pacora Portella, Percy (2015)
Diabetes mellitus is a state of impaired glucose tolerance, caused by inadequate or ineffective insulin secretion action thereof. This altered metabolic state may worsen during pregnancy because pregnancy causes changes in metabolism of carbohydrates, fats and proteins that can aggravate diabetes in patients with a genetic predisposition for the disease.